Analysis of potential neuropharmacological activity and attenuating effect in chronic constriction induced neuropathic pain using Calotropis procera (Aiton) Dryand flower ethanol extract - Ashutosh Kumar; Brijesh Kumar; Rajesh Kumar; Vinod Tiwari; Pratistha Singh; Ajay Kumar; Manish Singh; Chandra Shekhar Azad; Ankit Uniyal (Pharmacological Research - Modern Chinese Medicine)
Background: Calotropis procera, also known as ''毒竹 du zhu'' in Chainese, is used in several remedies to treat a variety of ailments, including inflammatory diseases, skin concerns, pain disorders, and respiratory issues. It has been observed that the various parts of the plant have been traditionally used for as anti-inflammatory and neuroprotective actions. The flower of this herb has not been investigated for these pharmacological properties. Purpose: The aim of this research is to investigate the neuropharmacological profile and ameliorative potential of ethanolic extract of C. procera flower (EECP) in chronic constriction injury (CCI) induced neuropathic pain in rats. Methods: GCMS analysis was performed to identify the active phytocmpounds of the plant. Neuropharmacological profile has been investigated by maximal electroshock seizure and pentylenetetrazole for antiepileptic, elevated maze plus and open field test for anxiety, tail suspension and forced swim test for depressant activity, and acetylcholinesterase and Morris water maze test for cognition. Anti-neuropathic pain was assessed via heat hyperalgesia and mechanical allodynia tests in rats after inducing CCI. Pro-inflammatory mediators (TNF-α, IL-1β, and IL-6) were determined by ELISA kits. SOD and nitrile level were measured for antioxidant activity. Sciatic nerve’s histopathological changes for nerve deformity were evaluated by H &E staining. Results: GCMS analysis revealed the presence of phytocompounds Lupeool, acetate, n-hexadecanoic acid, γ-sitosterol, hexadecanoic acid methyl ester, Octadecenoic acid (Z)-, methyl ester, β-Amyrin, phytol and other compounds. In neuropharmacological profile, EECP had a significant anticonvulsant effect, a decrease in locomotor activity, indicating a sedative effect but showed no anxiolytic effect. The immobility time decreased significantly in both the forced swim test and tail suspension test. The activity of acetylcholinesterase in the brain was decreased and Morris water test results revealed a shorter escape latency and greater time spent in the target quadrant. In anti-neuropathic pain assessment, the EECP reduced CCI-induced hyperalgesia and mechanical allodynia. TNF-α, IL-1β, and IL-6 levels were reduced while SOD levels increased and nitrite levels decreased in the sciatic nerve. Histological analysis revealed sciatic nerve deformity was reduced. Conclusion: It is concluded that extract showed a potent antiepileptic, antidepressant, cognition enhancer and protective against nerve deformity and neuropathic pain. Phytocompounds identified via GCMS having neuroprotective, antioxidant, and anti-inflammatory properties, which may be correlated with the neuropharmacological and analgesic activities of the extract.